Symbiotic nitrogen fixation in two species of leguminosae : Lathyrus maritimus (L) Bigel. and Oxytropis campestris (L) DC - Barimah-Asare, John (Memorial University of Newfoundland, 1991)
The symbiotic association of Rhizobium strains and two species of legumes, Lathyrus maritimus (L.) Bigel. and Oxytropis campestris (L.) DC found in subarctic regions of Newfoundland were investigated. The root nodule bacteria were isolated and routinely characterized using standard techniques for Rhizobium species. The isolate of L. jnaritimus was found to resemble fast-growing Rhizobium leguminosarum biovar vicia, except in its ability to tolerate a wide range of pH and a high concentration of NaCl. The isolate of 0. Campestris exhibited characteristics which resembled those of both slow-growing and fast-growing strains. Both isolates could grow, although slowly, at a low temperature (5°C). -- Cross inoculation tests were performed using the isolates on other legume species. The isolate of O. campestris could not infect any of the hosts used while that of L. maritimus could infect Vicia cracca. -- Growth patterns and external morphology of the symbiotic root nodules were studied. The beaded structure of field-collected nodules indicate that they resume growth after overwintering annually. The results of laboratory-grown specimens showed that nodules of both species attain a maximum size after which no growth occurs. Nitrogen fixation was assessed in the legumes using the acetylene reduction method with nodulated root systems. The two species showed highest nitrogenase activity at 20°C and were still capable of activity at low tempertures; for example, nodules of L. maritimus and 0. campestris were able to maintain 35% and 80% of their maximum activities respectively at 5°C, showing their adaptation to nitrogen fixation in the cold. -- The anatomy of L. maritimus root nodules was studied using light and electron microscopy. They were found to possess a zonal differentiation from the tip to the point of attachment to the root; i.e. the meristem, invasion zone, early symbiotic zone, late symbiotic zone and the senescent region. Nodules possessed lipid bodies which were more abundant in the cortical cells. The ...